PBBâP2 DIALIHKAN SECARA BERTAHAP DARI PEMERINTAH PUSAT KE PEMERINTAH DAERAH - Sulistyani, Tri (PERMANA, 2013)
Land and Building Tax (PBB) is a state tax imposed on the land and or buildings. Under Article 185 of Law No.. 28 of 2009 on Regional Taxes and Levies, since January 1, 2010, the management of land and building tax Rural and Urban Sector (PBB P-2) was transferred from central government to local governments, or from previously classified as central taxes to the local tax . The transfer of the management of PBB-P2 throughout the county / city begin no later than January 1, 2014. The transfer of the management of land and building tax Rural and Urban Sector (PBB-P2) is done in stages. With this transfer, all income from the PBB-P2 (100%) will go into local government. Keywords: Tax on Land and Building Rural and Urban Sector